The Legal Nature and Content of the “Presumption”of Illicit Origin of Property - Markosyan, Tigran (Bulletin of Yerevan University C: Jurisprudence, 2024)
The civil confiscation proceedings is a novelty in Armenian legal system and the comprehensive study of both complex and individual issues hold significant relevance. In this regard, the issues of the presumption of illegal origin of property is of particular importance, as its proper application is crucial for achieving a balance between public and private interests, as well as for ensuring human rights protection. This work is based on international documents, domestic legislation, and procedural studies, outlining the general proceedings for confiscating property deemed to have an illicit origin, its stages, the nature of evidentiary presumptions and their procedural significance, the conditions under which the presumption of illegal origin is applied, and the implications of this presumption. It also addresses the concept of "balancing of probabilities" relevant to these proceedings, or the criterion of "preponderance of evidence." In conclusion, the findings presented in this article may provide valuable insights for the ongoing development of legal practice and the refinement of existing regulations.